Establishing and augmenting views on the acceptability of a paediatric critical care randomised controlled trial (the FEVER trial): a mixed methods study. Issue 3 (10th March 2021) - Deja, Elizabeth; Peters, Mark J; Khan, Imran; Mouncey, Paul R; Agbeko, Rachel; Fenn, Blaise; Watkins, Jason; Ramnarayan, Padmanabhan; Tibby, Shane M; Thorburn, Kentigern; Tume, Lyvonne N; Rowan, Kathryn M; et al.
Abstract : Objective: To explore parent and staff views on the acceptability of a randomised controlled trial investigating temperature thresholds for antipyretic intervention in critically ill children with fever and infection (the FEVER trial) during a multi-phase pilot study. Design: Mixed methods study with data collected at three time points: (1) before, (2) during and (3) after a pilot trial. Setting: English, Paediatric Intensive Care Units (PICUs). Participants: (1) Pre-pilot trial focus groups with pilot site staff (n=56) and interviews with parents (n=25) whose child had been admitted to PICU in the last 3 years with a fever and suspected infection, (2) Questionnaires with parents of randomised children following pilot trial recruitment (n=48 from 47 families) and (3) post-pilot trial interviews with parents (n=19), focus groups (n=50) and a survey (n=48) with site staff. Analysis drew on Sekhon et al 's theoretical framework of acceptability. Results: There was initial support for the trial, yet some held concerns regarding the proposed temperature thresholds and not using paracetamol for pain or discomfort. Pre-trial findings informed protocol changes and training, which influenced views on trial acceptability. Staff trained by the FEVER team found the trial more acceptable than those trained by colleagues. Parents and staff found the trial acceptable. Some concerns about pain or discomfort during weaning from ventilation remained. Conclusions: Pre-trial findings and pilot trial experience influenced acceptability, providing insight into how challenges may be overcome. We present an adapted theoretical framework of acceptability to inform future trial feasibility studies. Trial registration numbers: ISRCTN16022198 and NCT03028818 .